A diversidade, a luminosidade e a turbidez determinam locais ecologicamente únicos para comunidade de algas e cianobactérias em microecossistemas naturais de água doce. - Souza, Yasmin Rodrigues de (2021)
Partitioning patterns of dissimilarity (beta diversity) into contributions of single sites or individual species is a modern approach to understanding what the main factors affect and cause variation in biodiversity. In this context, estimating the contributions of single sites to overall beta diversity (LCBD) or into contributions of individual species to overall beta diversity (SCBD) has proven to be a good approach to improve the knowledge of drivers of beta diversity. We explored the contributions of each site and species to the overall algae and cyanobacteria beta diversity of 77 natural freshwater micro-ecosystems (i.e., tank bromeliads) of a neotropical ecosystem. We found that LCBD was negatively affected by Shannon's diversity, turbidity, and luminosity (% canopy cover). Cyanobacteria and green algae were the groups that most contributed SCBD values. The negative relationship between LCBD and the Shannon index indicates that micro-ecosystems with less diversity reflect unique characteristics, and LCBD values can easily predict these environments. LCBD values can indicate these environments as priorities for management and conservation.